ANALISIS SEMIOTIKA PESAN DAKWAH DALAM PUISI “SAJADAH PANJANG” KARYA TAUFIQ ISMAIL - Fatma Laili Sa’adah, Zukha; Fakhruddin Fajrul Islam, Ahmad (Universitas Hasyim Asy'ari, 2024)
The literary works of Taufiq Ismail, an Indonesian cleric and writer, embed Islamic values within his creations, including the poem